Investigating the Modern Tamil Grammar of Vallinam and Mellinam Used by Tamil Lyricists Between 1952 and 2023 Using the Latin Square Design and the Levenshtein Distance. - Gnana Prakasam Louis Raja, Saviour Prakash; Venkatesan, Ramalingam Viswanathan (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This paper focuses on how the grammatical categories of a topologically generalised Tamil language emerge and are organised. The study of grammatical categories is explained by the notion of grammaticalization. The Levenshtein distance is a string metric used to quantify the dissimilarity between two se- quences in the fields of information theory, linguistics, and computer science? The amount of single-character changes needed to transform one word into another is the informal definition of the Levenshtein distance between those words. In this effort, we have tried to learn the linguistic intricacies of the Meyyeluttukal in Tamil language. Researchers in managed languages have made strides toward these ends by employing quantitative techniques for de- riving reliable conclusions of the Latin Square Design was used to compare the frequency of occurrence of Vallinam, Mellinam, and Idaiyinam in the work of several Tamil lyricists. The emphasis is on how the aforementioned grammatical framework is employed in both written and spoken conversation. Furthermore, we have investigated ANOVA for all of the factors involved in the development of language. In light of the findings, we have arrived at some realistic conclusions.